Methods of measuring the effectiveness of logistics activities - Robert Dmuchowski (Contemporary Economics, 2021)
Companies which wish to operate on the market must constantly discover and shape new potentials and abilities to create benefits that might ensure them long-term increase in efficiency and development. One of the ways to gain economic advantage is to reduce costs in all possible areas of their generation and maximize consumer satisfaction through more efficient and rational flow of primary products and goods (Manzouri &, Ab Rahman, 2013). Logistics, understood as a modern management concept, allows to achieve such economic and market effects. Comprehensive management of all activities related to material flows, goods or services from supply sources to users of finished products brings benefits in reducing total costs, which results in better economic results. Companies use various sets of indicators for measuring economic and operational efficiency and the most commonly used ones are profitability rates. The main goal of the article is to present an assessment of the efficiency of logistics processes based on the unit costs which arise in the areas recognized as logistic. The research problem is to indicate the method of measurement in order to examine the relationship between logistics management and the reduction of total costs and thus to study the impact of supply chain management on the efficiency and effectiveness of an economic entity. The applied research method is based on calculating the value of logistic cost-effectiveness coefficients and presenting them in dynamic terms. Lower values of the logistic cost-effectiveness coefficients will mean better logistic effects and more rational use of resources. The use of the presented measurement methods will allow company managers to create the most optimal supply chains in their business ventures. The article presents the cost-effectiveness rates calculated for logistics processes in the period 2018-2019 in the Large-area Multi-Branch Materials Warehouse in Kutno (centrally located, modern logistics warehouse) and the Materials Warehouse Jawidz.
Keywords: C61; C83; D24; D61; O12; 330; Logistics management; logistics processes; efficiency